Tren Penelitian Pembelajaran Sejarah di Luar Kelas (Outdoor Story Education): Sebuah Analisis Bibliometrik - Felisa Dwi Saharani; Fathina Auliya Shidqi; Syifaul Ummah (Lembaga Yasin AlSys, 2026)
History learning in schools is still often perceived as less interesting because of the dominance of lecture methods and the limited variation of classroom learning. This condition has encouraged the development of the Outdoor History Education approach, which utilizes the environment and real historical sources as contextual learning media. As attention to this approach increases, studies that map the development and tendencies of existing research are needed. This study aims to analyze research trends in outdoor history learning through a bibliometric approach. This study used a descriptive qualitative method with bibliometric analysis of relevant scientific articles. Data were collected through searches of online scientific journals and analyzed based on year of publication, research focus, and research characteristics. The results showed that publications on Outdoor History Education have developed fluctuatingly but have tended to increase in recent years. The research focus was dominated by studies on the use of the environment as a learning resource and its impact on students’ motivation and engagement. However, the number of studies remains relatively limited, and methodological variation has not developed optimally. The conclusion of this study affirms that Outdoor History Education has great potential to be developed as a contextual, interactive, and meaningful history learning approach. These findings contribute to expanding the mapping of outdoor history learning studies and provide implications for educators and researchers in developing more varied learning and research designs in the field of history education.